Phenolic Content and Antioxidant and Antimicrobial Activities of Malva sylvestris L., Malva oxyloba Boiss., Malva parviflora L., and Malva aegyptia L. Leaves Extract - Khalid A. Shadid; Ashok K. Shakya; Rajashri R. Naik; Nidal Jaradat; Husni S. Farah; Naeem Shalan; Nooman A. Khalaf; Ghaleb A. Oriquat (Journal of Chemistry)
Background. The plants brought by Arabs were of real therapeutic values. Ibn Al-Baitar, an Islamic scholar (pharmacist, botanist, and physician), in his encyclopedia wrote the detailed characterization of more than one thousand herbs describing their medicinal value, methods of preparation, and their route of administration. Objectives. The current investigation points towards the quantitative characterization of the phenolic contents among the four edible Malva plants species (Malva sylvestris L., Malva oxyloba Boiss., Malva parviflora L., and Malva aegyptia L.) and also towards assessing their antibacterial activity against one Gram-positive isolate (Staphylococcus aureus) and four Gram-negative strains Escherichia coli, Pseudomonas aeruginosa, Shigella sonnei, and Proteus vulgaris. It also aimed to evaluate the free radical scavenging activity of hexane, methanolic, aqueous, and acetone extracts of four Malva species. Methods. By utilizing the Folin–Ciocalteu procedure and gallic acid as a reference molecule, the phenolic contents were estimated. In addition, the broth microdilution method was used to evaluate four plants’ 16 extracts, and the DPPH (2,2-diphenyl-1-picrylhydrazyl) method was utilized to assess the abovementioned extracts against oxidative stress. Results. The results showed that the methanolic extract of M. oxyloba has the highest contents of phenols (191.54 ± 2.84 mg of GAE/g) and has the best antioxidant capacity with an IC50 value of 1.94 ± 1.84 µg/ml, which is very close to Trolox. Regarding the ferrous ion chelating activity of the extract, the methanolic extract of M. sylvestris exhibits appreciable activity with IC50 values of 52.7 ± 1.8 µg/ml. In addition, the plant extract and acetone extract of M. sylvestris showed a strong antibacterial activity with an MIC value of 0.0078 mg/ml. Conclusion. The methanolic extract of M. oxyloba has a pharmacological potential as a valuable natural product that can be utilized as a main ingredient in the design and development of new therapeutic formulations. It exerts multiple inhibitory properties against oxidative stress and bacterial growth. As such, it is emerging as a promising therapeutic agent for the treatment of various neurodegenerative diseases and many types of human infectious diseases.